2010
DOI: 10.3116/16091833/11/2/107/2010
|View full text |Cite
|
Sign up to set email alerts
|

Optical properties and local structure of (As2S3)100-x(SbSI)x glasses

Abstract: We report experimental results for the spectral dependences of the optical absorption edge in (As 2 S 3 ) 100-x (SbSI) x (0 ≤ x ≤ 90) glasses. Our studies have shown that increasing of antimony sulfoiodide (SbSI) content in the glass composition and the temperature increase lead to shift in the absorption edge towards long-wavelength range. The optical absorption edge

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…During the study of As 2 S 3 -SbSI system glasses by using methods of X-ray diffraction and Raman spectroscopy their nanoheterogeneous structure was established [6][7][8]. It has been shown that their matrix is formed only by binary structural groups with heteropolar bonds (AsS 3 , SbS 3 , SbI 3 , AsI 3 ) and also contains molecular fragments with homopolar As-As and S-S bonds.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…During the study of As 2 S 3 -SbSI system glasses by using methods of X-ray diffraction and Raman spectroscopy their nanoheterogeneous structure was established [6][7][8]. It has been shown that their matrix is formed only by binary structural groups with heteropolar bonds (AsS 3 , SbS 3 , SbI 3 , AsI 3 ) and also contains molecular fragments with homopolar As-As and S-S bonds.…”
Section: Resultsmentioning
confidence: 99%
“…Crystallization of glasses is accompanied by a sharp change in the optical and dielectric parameters [6,7]. The structure of the phase which occurs during the crystallization of glasses of the given system, corresponds to the structure of crystalline SbSI [6].…”
Section: Introductionmentioning
confidence: 99%
“…Absorption spectroscopy revealed that the optical band-gap of the synthesized glasses and Sb 2 S 3 crystals is different with values 2.1 and 1.7 eV, respectively [17,18]. To cause absorption of the laser beam enough for heating of glasses but relatively small by crystal, we selected a CW diode laser with intermediate wavelength of 639 nm (i.e.…”
Section: Methodsmentioning
confidence: 99%